Resepsi Al-Qur’an di Ponpes Muallimin Tahfizul Qur’an Sawah Dangka Agama - Muhammad Taufiq; Rahima Sikumbang (Journal on Education, 2022)
This study aims to find out the variety of Al-Qur'an receptions in the Islamic boarding school, as well as trying to understand the values ​​inherent in it. This research was designed using qualitative methods and included in the type of field research (field research). In obtaining data, researchers used various instruments, such as interviews, observation, and documentation. The analysis that researchers use is in the form of data reduction, data display, and drawing conclusions. From the research conducted, it shows that: (1) the variety of Al-Qur'an receptions in the Islamic boarding school include, firstly exegesis receptions in the form of thematic interpretation studies, secondly aesthetic receptions manifest in calligraphy in the teacher's room, dormitory and caregiver's room, while Functional receptions are manifested in the recitation of selected letters and eternal receptions are manifested in various Qur'anic preservation practices, such as memorizing verses in the form of sima'an and muraja'ah. The values ​​inherent in the variety of receptions include: objective values, expressive values, and documentary values. objectively concludes that the variety of reception behavior at the Islamic boarding school is a symbol of obedience to the rules of the Islamic boarding school. Its expressive value is a form of self-internalization with positive things through a continuous process of learning the Qur'an and its documentary value is a form of local contextualization of comprehensive cultural system